KINETIC STUDY USING FREE DRAINING LEACH COLUMN TEST AND HUMIDITY CELL TEST METHODE FOR PREDICTING ACID MINE DRAINAGE GENERATING IN COAL MINE - FAJARWATI (NIM : 22108301), AYI
Three rocks samples coming from PIT (fresh rock) and overburden disposal coal mine of Lati Site PT. Berau Coal (East Kalimantan, Indonesia) were tested by two methods those are the Humidity Cell Test (HCT) and Free Draining Column Leach Test (FD). The objectives from this research was to to compare the result from leacheate simulation on Free Draining and Humidiy Cell Test Methods by analyze sulfide mineral oxydation rate and to identify several control parameters those were influence leacheate quality result and oxydation rate on different kinetic test. First step before kinetic test, static test was conducted and showed that each rock samples has different Acid Generating Potential. The three rock samples (PIT WEST, DISPOSAL Q10, PIT EAST) that used at this research was sort of low PAF(Potentially Acid Forming) group (PIT WEST), medium PAF group (DISPOSAL Q10) and high PAF group (PIT EAST). The result of research showed pH level at near neutral in PIT WEST sample, and acid pH for another samples. Kinetic test method is using uniform particle size distribution. Geochemical parameter from leachate produced was examined for each cycle in every kinetic test. From both of the simulation showed that analytical pyrite weathering rate result at each rock samples seen significant from FD test more than HCT test.